Do socio-economic factors impede the engagement in online banking transactions? Evidence from Ghana - Abdul Bashiru Jibril; Michael Adu Kwarteng; Miloslava Chovancová; Jurgen Bode (Banks and Bank Systems, 2020)
Researchers have long pondered on the online banking transaction adoption. Some of these studies focus primarily on the motivating factors that affect customers’ intention to adopt/accept these services (technologies). However, research into the constraining factors, in particular socio-economic factors, barely exist in the literature, especially in the context of sub-Saharan Africa. Against this background, the paper seeks to fill in this gap by: (1) assessing the socio-economic factors impeding the engagement of e-banking transactions among retail bank customers in Ghana, and (2) examining the moderating effect of ‘customer experience of Internet’ on the identified factors that inhibit the engagement in online banking in Ghana. The paper used a quantitative research approach to obtain data from two leading Ghanaian banks. Out of the 450 questionnaires distributed, 393 were valid for analysis. Data were analyzed with the aid of PLS-SEM (partial least squares and structural equation modeling). Findings revealed that perceived knowledge gap and the price of digital devices were directly important to the intention to disembark on e-banking transactions among Ghanaian bank customers. Whilst customer experience (frequent use of the Internet), as a moderator variable, has a significant effect on the interaction between perceived knowledge gap and the intent to disembark on e-banking transactions; and finance charges and the intent to disembark on e-banking transactions. Study implications and directions for future research are discussed in the paper. AcknowledgmentThis work was supported by the Internal Grant Agency of Tomas Bata University under the Projects no. IGA/FaME/2019/008 and IGA/FaME/2020/002. The authors would like to extend their appreciation to Prof. Boris Popesko (Vice-dean for Research and Business Liaison) at the Faculty of Management and Economics for facilitating the financial readiness of this project.